TRUMP, TWITTER, AND TREASURIES - Peter Tillmann (Contemporary Economic Policy, 2020)
After appointing Federal Reserve Chairman Powell, President Trump put pressure on the Fed to cut interest rates. We show that, on average, a statement from Trump on the Fed led to lower long-term interest rates, consistent with expectations of lower expected future short rates. However, the impact of Trump's statements declined over time. (JEL E52, E43, E32)
Keywords: 330